2003
DOI: 10.1086/379015
|View full text |Cite
|
Sign up to set email alerts
|

Once-Weekly Dalbavancin versus Standard-of-Care Antimicrobial Regimens for Treatment of Skin and Soft-Tissue Infections

Abstract: Dalbavancin, a novel glycopeptide with a long elimination half-life ( approximately 9-12 days), was compared to standard antimicrobial therapy for skin and soft-tissue infections (SSTIs). In a randomized, controlled, open-label, phase 2 proof-of-concept trial, adults received 1100 mg of dalbavancin (as a single intravenous infusion), 1000 mg of dalbavancin intravenously and then 500 mg intravenously 1 week later, or a prospectively defined standard-of-care regimen. A gram-positive pathogen was isolated from sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
145
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(154 citation statements)
references
References 8 publications
4
145
0
5
Order By: Relevance
“…Dalbavancin has a prolonged halflife of 6 to 10 days and can potentially be administered as 2 doses 1 week apart. 99 It is currently being studied in phase 3 trials for the treatment of ABSSSIs. 100 Another lipoglycopeptide, oritavancin, is being investigated for ABSSSIs and has the potential to be used as single-dose therapy.…”
Section: Treatment Failurementioning
confidence: 99%
“…Dalbavancin has a prolonged halflife of 6 to 10 days and can potentially be administered as 2 doses 1 week apart. 99 It is currently being studied in phase 3 trials for the treatment of ABSSSIs. 100 Another lipoglycopeptide, oritavancin, is being investigated for ABSSSIs and has the potential to be used as single-dose therapy.…”
Section: Treatment Failurementioning
confidence: 99%
“…In skin and soft tissue infections, a 92-94% microbiological and clinical response respectively was found in an open label phase 2 comparative dosing trial. 73 Clinical success at follow-up visits for the two dose dalbavancin group was 80% for MRSA versus 50% for comparator therapy (which included beta-lactams, clindamycin, vancomycin and linezolid, respectively).…”
Section: Dalbavancinmentioning
confidence: 92%
“…This antibiotic has been evaluated for catheterrelated bacteremia 72 and skin and soft tissue infections. 73 Dalbavancin was effective and well tolerated in adult patients with catheter-related bacteremia caused by coagulasenegative Staphylococci, MSSA and MRSA in a comparative trial with vancomycin. In skin and soft tissue infections, a 92-94% microbiological and clinical response respectively was found in an open label phase 2 comparative dosing trial.…”
Section: Dalbavancinmentioning
confidence: 97%
“…The adoption of an updated test-of-cure clinical response (C90 % reduction in lesion size, no increase in lesion size since day 3, and no requirement for additional antibacterialcs/significant surgical procedures) concluded that there was equivalence between telavancin-and vancomycin-treated patients (68.0 vs. 63.3 % cure rates). Phase II studies determined the optimal dosing regimen as being a single dose of 1200 mg for oritavancin (SIM-PLIFI trial [3]), a 1000 mg dose at day 1 followed by a 500 mg dose at day 7 for dalbavancin [136], and a 10 mg/ kg daily dose for telavancin (FAST 2 trial [137]). Thus, a possible advantage of oritavancin and dalbavancin resides in their simplified therapeutic scheme, which may even allow their use for home therapy [138,139].…”
Section: Registered Indicationsmentioning
confidence: 99%